An inter-comparison of black-carbon-related instruments in a laboratory study of biomass burning aerosol. Issue 11 (2nd November 2018) - Tasoglou, Antonios; Subramanian, R.; Pandis, Spyros N.
Abstract: Black carbon (BC)-containing particles are the most strongly light absorbing aerosols in the atmosphere. Measurements of BC are challenging because of its semi-empirical definition based on physical properties and not chemical structure, the complex and continuously changing morphology of the corresponding particles, and the effects of other particulate components on its absorption. In this study, we compare six available commercial continuous instruments measuring BC using biomass burning aerosol. The comparison involves a Soot Particle Aerosol Mass Spectrometer (SP - AMS), a Single-Particle Soot Photometer (SP2), an aethalometer, a Multiangle Absorption Photometer (MAAP), and a blue and a green photoacoustic extinctiometer (PAX). An SP-AMS collection efficiency equal to 0.35 was measured for this aerosol system. The corrected SP-AMS BC mass measurements agreed within 6% with the SP2 refractory BC mass values. Two regimes of behavior were identified for the optical instruments corresponding to high and low organic/BC ratio. The mass absorption cross-sections (MAC) measured varied from 26% to two times the instrument default values depending on the instrument and the regime. The presence of high organic aerosol concentration in this system can lead to overestimation of the BC mass by the optical instruments by as much as a factor of 2.7. In general, the discrepancy among the BC measurements increased as the organic carbon content of the BC-containing particles increased. © 2018 American Association for Aerosol Research